Effects of Plant Media And Fertilization on The Growth of Orchid Plant (dendrobium sylvanum rchb. F.) in Acclimatization Phase - Sucipto Hariyanto; Ahmad Ridlwan Jamil; Hery Purnobasuki (Universitas Muhammadiyah Yogyakarta, 2019)
This study was to evaluate the effect of plant media variation, time of fertilization, and combination of both on the growth of orchid plant Dendrobium sylvanum Rchb. f. in acclimatization phase. This study was designed using 6x4 factorial experimentation. The first factor was the variation of plant media: charcoals, coconut husk, bagasse, mixing of charcoal and coconut husk, combination of charcoal and bagasse, combination of coconut husk and bagasse. The second factor was fertilization time: no fertilization, 7 day-fertilization, 14 day-fertilization, and 20 day-fertilization for three months. The data were analysed by using Two Way MANOVA (α = 5%) and Duncan test. Based on the results, there were differences between media variation and fertilization time on the increase of leaf length and width, stem diameter, and root length of Dendrobium orchid in acclimatization phase. Combination of bagasse and coconut husk media showed the best result on media treatment. The best of fertilization time was 14 days. Moreover, the best of interaction between media and fertilization time showed by the combination of bagasse and coconut husk with 14 days-fertilization.